IDENTIFIKASI GUGUS FUNGSI ASAP ROKOK DENGAN PENAMBAHAN ANTIOKSIDAN ALAMI - Rohul Hayati (Universitas Citra Bangsa, 2018)
Cigarettes have a lot of radical content, especially in smoke that is accumulated. But the consumption of cigarettes in the community, actually increases every year. Compounds that can counteract radicals are antioxidants. Natural antioxidants are the main choice because there are no negative side effects arising from their use. This research was conducted with the aim to identify functional groups of compounds in cigarette smoke without the addition of antioxidants and with the addition of antioxidants. The research design used is pure experimental research. The cigarettes used are commercial cigarettes that are sold freely on the market. While the antioxidants used are natural antioxidants obtained from juwet (Syzygium cumini) fruit extract. The results obtained indicate that the cigarette smoke function group with the addition of antioxidants is more stable than cigarette smoke without the addition of antioxidants. This means that radical compounds in cigarette smoke have decreased after adding antioxidants in the filter section Keywords: cigarette smoke, radical compound, antioxidant, compound function group